Three Dimensional Frequency Selective Surface With Band-Reject Multiple Transmission Zero And Pseudo-Elliptic Response - Dutta, Bimal Raj; Kanaujia, Binod Kumar; Dalela, Chhaya (Institute of Advanced Engineering and Science, 2019)
The three-dimensional Frequency Selective Surface (3D FSS) with band reject multiple transmission zeros and pseudo-elliptic response is designed from two-dimensional (2D) periodic array of shielded micro strip lines to realize wide out-of –band radio wave rejection. This 3D FSS array consists of multimode cavities whose coupling with air can be controlled to obtain a desired frequency range. The proposed FSS with shorting via to ground exhibits pseudo-elliptic band-reject response in the frequency range from 6GHz to 14GHz. As the plane wave of linear polarization incidents perpendicularly to the shielded micro strip line with perfect electric conductor (PEC) and perfect magnetic conductor (PMC) boundary walls, two quasi-TEM modes are obtained known as air mode and substrate mode. The designed 3D FSS is a combination of two or more resonators. Furthermore, second 3D FSS design with three shorting via result more elliptic band reject frequency response and a pass band transmission pole. The in phase resonators of design give transmission poles and out of phase combination of resonators give transmission zeros respectively. The proposed 3D FSS is designed and simulated using Ansys HFSS software. The 3D FSS designs with wide out-of-band rejection and stable frequency response exhibit an improved performance over 2D FSS for many practical applications such as antenna sub-reflector, radomes and spatial filters.